Drugs of abuse. (March 2016) - Hill, Simon L.; Thomas, Simon H.L.
Abstract: Toxicity related to drug misuse is a common reason for hospital presentation. The recent emergence of substantial numbers of novel psychoactive substances has made management more challenging because the exact constituents of branded products containing these may not be known and, when it is, the information available about clinical features and the management of toxicity is limited. Drugs of misuse are usefully classified by their primary clinical effects. Depressants including opioids, benzodiazepines and gamma-hydroxybutyrate cause sedation with depressed tendon reflexes. Commonly encountered stimulants are cocaine, amphetamines, methylenedioxymethamphetamine ('ecstasy'), cathinones (e.g. mephedrone), piperazines, piperidines and NBOMe compounds. Typical effects include tachycardia, hypertension, mydriasis, agitation and seizures. Examples of hallucinogens are synthetic cannabinoid receptor agonists, tryptamines (e.g. alpha methyltryptamine) and ergolines (e.g. lysergic acid diethylamide); some of these also have stimulant effects. The arylcyclohexamines ketamine and methoxetamine have dissociative actions. As well managing acute toxicity, blood-borne infections, sepsis and thrombosis arising from parenteral drug use should be treated. Longer term interventions are also needed to address drug use and the social and mental health issues that commonly co-exist.